International humanitarian ngos and state relations - Cunningham, Andrew J., author.
1 online resource (224 pages)
Keywords: International Humanitarian NGOs and State Relations: Politics, Principles and Identity examines the often discordant relationship between states and international non-governmental organisations working in the humanitarian sector. INGOs aiming to provide assistance to populations su?ering from the consequences of con?icts and other human-made disasters work in the midst of very politically sensitive local dynamics. The involvement of these non-political international actors can be seen as a threat to states that see civil war as a state of exception where it is the government’s prerogative to act outside ‘normal’ legal or moral boundaries. Drawing on ?rst-hand experience of humanitarian operations in contexts of civil war, this book explores how the relationship works in practice and how often clashing priorities can be mediated.